The effect of immature adult-born dentate granule cells on hyponeophagial behavior is related to their roles in learning and memory - Deng, Wei; Gage, Fred H. (Frontiers in Systems Neuroscience, 2015)
The neurogenesis hypothesis of depression is based on the correlation between the rate of adult hippocampal neurogenesis and the affective status of rodents. However, studies investigating the role of neurogenesis in the causation of mood regulation have reported inconsistent results. Here, we explored whether the affective state can be affected differentially by adult-born neurons with distinctive physiological characteristics at different maturation stages. We revealed that reducing the immature newborn neuron population had no effect on anxiety- or depression-like behaviors in an array of tests; however, it enhanced hyponeophagia in a novelty suppressed feeding test, but only when the novel environment was drastically different from the home cage. We further demonstrated that reducing the immature newborn neuron population led to delayed habituation to a novel environment and impaired contextual learning. Hence, rather than being directly involved in mood regulation, our studies raise the possibility that adult neurogenesis may influence hyponeophagia through its role in mnemonic processing.